Advances in miR-132-Based Biomarker and Therapeutic Potential in the Cardiovascular System - Xu, Kaizu; Chen, Chungui; Wu, Ying; Wu, Meifang; Lin, Liming (Frontiers in Pharmacology, 2021)
Atherosclerotic cardiovascular disease and subsequent heart failure threaten global health and impose a huge economic burden on society. MicroRNA-132 (miR-132), a regulatory RNA ubiquitously expressed in the cardiovascular system, is up-or down-regulated in the plasma under various cardiac conditions and may serve as a potential diagnostic or prognostic biomarker. More importantly, miR-132 in the myocardium has been demonstrated to be a master regulator in many pathological processes of ischemic or nonischemic heart failure in the past decade, such as myocardial hypertrophy, fibrosis, apoptosis, angiogenesis, calcium handling, neuroendocrine activation, and oxidative stress, through downregulating target mRNA expression. Preclinical and clinical phase 1b studies have suggested antisense oligonucleotide targeting miR-132 may be a potential therapeutic approach for ischemic or nonischemic heart failure in the future. This review aims to summarize recent advances in the physiological and pathological functions of miR-132 and its possible diagnostic and therapeutic potential in cardiovascular disease.